Research on Issues for Mothers in Single-Mother Households to Become Independent - Rika Masuyama; Natsuko Minamino (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This research aims to review the literature relating to the issues for single-mother households to become independent based. Relevant articles were identified by searching the CiNii Resarch databases of articles published between 2000and 2022 examining support for the independence of single-mother households. We organized the viewpoints of "economy," "employment and childcare balance," "social support," "support system," and "independence required of single-mother households," which are the background of single-mother households. Predicted that mothers in single-mother households, who are in a state of economic poverty, will face multiple problems, such as unemployment, child-rearing, and "making ends meet" to survive on a low income. And mothers may have to reduce the time spent on recharging their personal resources (leisure and sleep) and use that for work and child-rearing. Therefore, their health will suffer. Since 2002, the government has four measures are being promoted: child-raising and livelihood support, employment support, securing child support expenses, and economic support. However, if comprehensive support for employment and self-reliance is to support self-help efforts without relying on others, it is a severe support measure for mothers of single-mother households who are already continuing self-help efforts.The current situation of single mothers has revealed that the issues faced by single-mother households are "economic poverty," "lack of self-investment by mothers," "lack of social support," "reluctance to receive social support," "inconsistency in support systems," and "self-help efforts required by society." It was suggested that there are the above problems.